Pelatihan Desain Grafis Menggunakan Aplikasi Adobe Photoshop Pada Ibu PKK Dan Karang Taruna Di Kelurahan Pancoran Mas Kota Depok - Saputro, Joko; Bani, Alexius Ulan; Nugroho, Fifto; Kurnia, Mega Tri (LPPM Universitas Bung Karno, 2022)
The readiness and accessibility of top-notch human resources must be harmonized with the current technology improvements and advancements. The country of Indonesia country, which has a population of around 275 million, has a lot of potential for developing its human resource base. However, preparing its human resources to compete in the global market is a challenge. Therefore, through partnership programs between educational institutions and various organizations, it is the best means of information transfer to increase knowledge and skills in the community. In order to carry out the Tri Dharma of Higher Education, the lecturers of the Computer System Study Program plan to conduct training activities in Pancoran Mas Village, Depok City. The lecturers of the Computer System Study Program at Bung Karno University plan to conduct training activities as part of the implementation of the Tri Dharma of Higher Education, this activity is carried out in Pancoran Mas Village, Depok City. This training activity was carried out in 2 time periods, namely on 21 and 28 July 2022 with the title graphic design training using Adobe Photosop software for PKK and Karang Taruna women, this training was attended by 11 participants consisting of 6 elements from PKK women and 5 participants from Karang Taruna elements. cadets. This activity is carried out using direct training and mentoring methods packaged into 3 learning models such as lectures, practice and sharing sessions, the results of this activity are able to provide new experiences, increase understanding, knowledge, and skills for participants in making a design object. The level of understanding of the original participants was 48.18% and at the end of the training participants were able to increase their understanding by 29.09% so that the understanding of participants now reaches 77.27%. This activity was successfully implemented and obtained satisfactory results based on the level of participant satisfaction of 72.4%.